Investigation of foot landing techniques and muscle activation during single-leg drop landings : implications for non-contact anterior cruciate ligament injuries - Teng, Phillis Soek Po (Nanyang Technological University, 2017)
Anterior cruciate ligament (ACL) injuries are common during sport, frequently occurring during non-contact situations, caused by the athletes’ own manoeuvres. The foot and ankle form the initial parts of the lower extremity kinetic chain during landing. Thus, foot landing positions can affect the force transmission from the ankle to the knee. Yet, many studies on ACL injuries have not focused on the ankle and this is considered a gap to the better understanding of non-contact ACL injuries. The roles of the gastrocnemius and hamstring in non-contact ACL injury risk reduction, especially during the pre-landing phase of single-leg landings are also still unclear. Therefore, investigation of foot-landing techniques and muscle activation during single-leg landings is an important area to provide new insights into non-contact ACL injury risk reduction.